Tax avoidance and tax evasion: study of taxation implementation in Indonesia - Deddy Sulestiyono; Maya Aresteria; Alfita Rakhmayani; Muhammad Syauqal Afwika Rahman (Proceeding International Conference on Accounting and Finance, 2026)
The conceptual difference between Tax Avoidance and Tax Evasion depends on the legality of the taxpayer’s actions. Tax Avoidance is a violation of the law: When taxpayers fail to report their taxable income, they are involved in an illegal activity that makes them liable for administrative or legal action by the authorities. In avoiding taxes, taxpayers are concerned about the possibility of their actions being detected. The objective of this study is to explain the fundamental process differences between Tax Avoidance and Tax Evasion based on a study of tax regulations in Indonesia. To address our research objectives, we conducted a Systematic Literature Review (SLR) of recent Tax Fraud cases ruling, sourced from Supreme Court databases. The results of this study indicate that Tax Avoidance is a practice carried out to reduce the tax burden legally. Although legal and in accordance with regulations, this practice is often considered unethical because it can harm state revenues. In contrast, tax evasion is an illegal act carried out to avoid paying taxes in a manner that violates the law. This can include not reporting all income, falsifying financial statements, or hiding assets. From the perspective of Taxpayers, as long as the tax avoidance is not prohibited, then it is permissible (legal).